Use of water generated by air conditioners for non-potable purposes - Melo, Allan Jayson Nunes de; Soares, Maria Carolina Duarte Marques; Silva , Simone Rosa da; Soares, Willames de Albuquerque (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This study aims to evaluate the feasibility of using condensate water from air conditioners for non-potable purposes in a hospital building located in the city of Recife-PE, Brazil. The applied methodology was divided into the following steps: investigation of the amount of water generated by the condensate, where it was used in three ways to observe the volume of water produced, the first through the collection with a graduated cylinder and application of equations, the second through hydrometers installed in the condensate drainage network and the third by installing a rain gauge with arduino in the equipment drain. The second methodological step was to take the non-potable consumption demands of the building to the points that consume garden watering, cooling towers and hospital hygiene by washing and mopping the floors. The results show that the equipment in the building has the potential to generate a significant amount of water, with an estimated value greater than 640 m³ if it were to collect water from all equipment. In some periods, the condensate water from all the equipment would be able to meet 92.6% of the building demand. These results are positive in relation to the amount of water produced by air conditioning equipment, in order to meet the demands that do not require potable water for their activities, thus presenting a new water source for buildings.